PENYUSUNAN RENCANA PEMBELAJARAN BAHASA ARAB BERDASARKAN KURIKULUM 2013 BAGI GURU-GURU BAHASA ARAB MADRASAH TSANAWIYAH SE-KABUPATEN KEBUMEN - Zukhaira, Zukhaira (Universitas Negeri Semarang, 2016)
This activitywas carried out with the aim to explain the importance of planning Arabic language learning based on Curriculum 2013 for teachers of Arabic in Madrasah Tsanawiyah throughout Kebumen district to improve the quality of Arabic language learning. It described the steps of the preparation of lesson planning (syllabus and lesson plan) based on curriculum 2013, and applied them in Arabic language teaching and learning activities in eachMadrasah Tsanawiyah. Alternative solution to these problems that have been applied in this community service was to conduct workshop and training. The conclusion that this activity was the implementation of community service was very useful for the Arabic language teachers in Madrasah Tsanawiyah throughout Kebumen district. With this training, teachers of Arabic Madrasah Tsanawiyahthroughout Kebumen district gained an increased understanding of the importance of the planninglessons based on the curriculum 2013 with the appropriate preparation of syllabi and lesson plans and gained solutions to some of the problems that they faced in learning the Arabic language, especially after the implementation of Curriculum 2013.